Dark Costs, Missing Data : Shedding Some Light on Services Trade - Anderson, James E.; Borchert, Ingo; Mattoo, Aaditya; Yotov, Yoto V. (World Bank, Washington, DC, 2015)
A structural gravity model is used to estimate barriers to services trade across many sectors, countries, and time. Since the disaggregated output data needed to infer border barriers flexibly are often missing for services, this paper derives a novel methodology for projecting output data. The empirical implementation sheds light on the role of institutions, geography, size, and digital infrastructure as determinants of border barriers. The paper finds that border barriers have generally fallen over time, but there are differences across sectors and countries. Notably, border effects for the smallest economies have remained stable, giving rise to a divergent pattern across countries.